The Urgency of Career Planning and Basic Services for Career Planning for Students at SMK Negeri 1 Cilegon - Meilla Dwi Nurmala; Poppy Asleha; Levana Meilani Mahmud; Rahmayanti Rahmayanti; Arnawati Arnawati; Nabilatuzzahra Nabilatuzzahra; Siti Nurshelomita; Ucu Muslihah; Sulaeha Sulaeha; Sulis Setiawati; Nela Agustin (Educare: Journal Educational and Multimedia, 2023)
Subject in this research is students at SMK Negeri 1 Cilegon, this school is one of the superior vocational high schools in the city of Cilegon, therefore graduates produced by this educational unit must of course be of high quality and able to meet job market expectations. This research aims to explain the urgency of career planning and find out the basic counseling services related to career planning needed by students at SMK Negeri 1 Cilegon. This research uses a qualitative approach with observation, literature study and assessment methods. The results of this research include: (1) the majority of class XII students at this school are faced with problems in the career field, especially career planning; (2) planning a career is important for students at SMK Negeri 1 Cilegon because having a career plan can certainly help them in making decisions, identifying and making the next steps to achieve their expected career goals, determining their major when wishing to continue their education, develop internal potential and be able to help him determine the expected job; (3) The basic counseling guidance service provided to students at SMK Negeri 1 Cilegon is by holding a seminar with the theme "The urgency of career planning for students at SMKN 1 Cilegon" which aims to enable students to understand the work environment or further studies related to their potential and understand regarding the type of work required and the type of education or training required for career development in a particular field.